Measuring functional, interactive and critical health literacy of Chinese secondary school students: reliable, valid and feasible?. (December 2018) - Guo, Shuaijun; Davis, Elise; Yu, Xiaoming; Naccarella, Lucio; Armstrong, Rebecca; Abel, Thomas; Browne, Geoffrey; Shi, Yanqin
Health literacy is an increasingly important topic in the global context. In mainland China, health literacy measures mainly focus on health knowledge and practices or on the functional domain for adolescents. However, little is known about interactive and critical domains. This study aimed to adopt a skills-based and three-domain (functional, interactive and critical) instrument to measure health literacy in Chinese adolescents and to examine the status and determinants of each domain. Using a systematic review, the eight-item Health Literacy Assessment Tool (HLAT-8) was selected and translated from English to Chinese (c-HLAT-8). Following the translation process, a cross-sectional study was conducted in four secondary schools in Beijing, China. A total of 650 students in Years 7–9 were recruited to complete a self-administered questionnaire that assessed socio-demographics, self-efficacy, social support, school environment, community environment and health literacy. Results showed that the c-HLAT-8 had satisfactory reliability (Cronbach's α = 0.79; intra-class correlation coefficient = 0.72) and strong validity (translation validity index (TVI) ≥0.95; χ 2 / df = 3.388, p < 0.001; comparative fit index = 0.975, Tucker and Lewis's index of fit = 0.945, normed fit index = 0.965, root mean error of approximation = 0.061; scores on the c-HLAT-8 were moderately correlated with the Health Literacy Study-Taiwan, but weakly with the Newest Vital Sign). Chinese students had an average score of 26.37 (±5.89) for the c-HLAT-8. When the determinants of each domain of health literacy were examined, social support was the strongest predictor of interactive and critical health literacy. On the contrary, self-efficacy and school environment played more dominant roles in predicting functional health literacy. The c-HLAT-8 was demonstrated to be a reliable, valid and feasible instrument for measuring functional, interactive and critical health literacy among Chinese students. The current findings indicate that increasing self-efficacy, social support and creating supportive environments are important for promoting health literacy in secondary school settings in China.